Forest elephants modulate their behavior to adapt to sounds of danger - Verahrami, Anahita K., author; Bombaci, Sara, advisor; Blanchard, Nathaniel, committee member; Wittemyer, George, committee member (Colorado State University. Libraries, 2023)
The African forest elephant (Loxodonta cyclotis) plays a critical role in upholding the structure and function of the Congo Basin, the world's second largest tropical forest which crucially contributes to global carbon sequestration. Research has demonstrated an 86% decline in forest elephant population numbers between 1990-2021, largely because of hunting for ivory. Due to the species' cryptic nature in their dense rainforest habitat, little is known on how they respond to human disturbances such as gun hunting. The studies that have been completed reveal that forest elephants may respond to disturbance by demonstrating changes in their abundance, distribution, and nocturnal activity. Changes in forest elephant distribution and activity not only have ramifications for the species' activity budgets, which when affected, may influence their foraging and reproductive behaviors and success, but may also impact the species' interspecific interactions with vegetation in certain areas, affecting forest growth and function. However, little is known on how a key population of this critically endangered species in the northern Republic of Congo is responding to disturbance such as hunting in the region. Using acoustic detection models in combination with a landscape-scale acoustic monitoring effort in and around Nouabalé-Ndoki National Park, Republic of Congo, I assess how forest elephant vocal activity is being influenced by gun hunting. Using these data, I examine (1) how forest elephant vocal activity changes across an eight-day period and (2) if forest elephants are shifting to more nighttime vocal activity following a gun hunting event. Results show that, on average, forest elephants are present and vocal at sites without gun events 53% of the time, but at sites with gun events, this value drops to 43%. Results also indicate that this change in activity following a gun hunting event is sustained over the eight-day period examined and does not vary from day-to-day. Results from the analysis exploring how the proportion of nighttime calling activity changes in response to gun hunting show that number of gunshots is an important predictor of nighttime vocal activity. Specifically, as the number of gunshots increase, there is a dramatic increase in the proportion of nighttime calling activity. Understanding the degree at which forest elephants are affected by gun hunting provides a convincing argument to focus limited conservation resources on developing more effective strategies to reduce indirect impacts from hunting on this critically endangered and ecologically important species.
Keywords: bioacoustics; conservation biology; gun hunting; Central Africa; acoustic monitoring; forest elephant